2021
DOI: 10.5194/bg-2021-60
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mediterranean seagrasses as carbon sinks: Methodological and regional differences

Abstract: Abstract. The increasing rates of CO2 due to anthropogenic activities are causing important potential climate threats for the Mediterranean Sea: ocean acidification and warming. In this region, two seagrass species, Posidonia oceanica and Cymodocea nodosa can play a crucial role in climate change mitigation. Through their metabolic activity, they can act as carbon sinks; buffer lowering pH values during the day and store carbon in the sediment underneath their meadows. In this study we analyse the metabolism s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…This method allows for an assessment of how different land use types affect carbon cycling. Previous research has shown that forests, grasslands, water bodies, and unused land have a significant capacity for carbon absorption [34], while cultivated land and construction contribute to carbon emissions. Given the direct impact of changes in land types, such as arable land, forest land, grasslands, water bodies, and unused land, on regional carbon emissions, the carbon emissions of these land types can be estimated using the carbon emission coefficient method.…”
Section: Direct Carbon Emission Estimationmentioning
confidence: 99%
“…This method allows for an assessment of how different land use types affect carbon cycling. Previous research has shown that forests, grasslands, water bodies, and unused land have a significant capacity for carbon absorption [34], while cultivated land and construction contribute to carbon emissions. Given the direct impact of changes in land types, such as arable land, forest land, grasslands, water bodies, and unused land, on regional carbon emissions, the carbon emissions of these land types can be estimated using the carbon emission coefficient method.…”
Section: Direct Carbon Emission Estimationmentioning
confidence: 99%
“…Increased sugar production increases palatability to herbivores (Arnold et al, 2012;Hernán et al, 2016). Additionally, although there is a clear correlation between seagrass metabolism and temperature (Escolano-Molto et al, 2021), an emerging body of evidence suggests that seedlings are not as robust as adults and are therefore more vulnerable to heat stress (Guerrero-Meseguer et al, 2017;Zimmerman et al, 2017).…”
Section: Unaborted Seeds Spathementioning
confidence: 99%